Pengaruh Efektivitas Pelayanan terhadap Kepuasan Konsumen pada Pelabuhan Speedboat Kayan II Tanjung Selor - Dedik Wiryawan (Faculty of Economics and Business Mulawarman University, 2017)
This research is aim to analyze effectiveness of services influences to customer satisfaction in Kayan speedboat port II Tanjung Selor. The study will use 88 respondents who are users of services Kayan speedboat port II Tanjung Selor. Analysis tool use Ordinary Least Square. Result of research is effectiveness of services variabel was give significant influence to consumer satisfaction variabel in Kayan speedboat port II Tanjung Selor. Testing result was using t test to show thitung ttabel (2.454 1.662). with test results can to knowing is research hypotesis which in explain research be accepted.Keywords: Effectiveness of service, consumer satisfaction